Effects of BAC on the Innervation of Stomach - Tarakçi, Berrin Gençer (My University, 2000)
Serosal application of BAC (benzalkonium chloride) to the pyloric antrum of the rat led to a complete loss of the intrinsic innervation of the treated region and also extensive loss of extrinsic sensory projections in the treated and untreated regions of the stomach. However, no changes were seen in the numbers of primary afferents projecting to the stomach, or expression of neuropeptides or neuronal proteins in the neurons. This finding is in marked contrast to the changes reported in sensory cell bodies after sectioning of the sciatic nerve, and suggested that visceral and somatic afferents may respond differently to axonal destruction.
Keywords: BAC (benzalkonium chloride); Intrinsic innervation; Primary afferents; Rat; Stomach